Women in Social Production (An Analysis of Some Sociological Investigation Data) - Panova, Nina (Problemos, 1968)
A high degree of female employment is characteristic of the Lithuanian SSR as well as on the whole of the Soviet Union. In 1967 the share of women in national economy grew to 48% against 29% in 1945. In the course of our investigation the level of education, qualification and labour efficiency of women in a number of Vilnius enterprises was analysed. The investigation showed that 56.5% of questioned female workers had incomplete or complete secondary education, while over 40% of women were still with incomplete secondary education and 22.6% with primary education. Female grades on an average are lower than those of men. The average grade index of men and women is 4.89 and 3.83 respectively. The insufficient level of qualification stipulates the employment of women in labour of lower qualifications. The majority of women questioned are engaged in monotonous, manual low qualified labour. The overwhelming majority of female workers (93.9%) do not take any schooling. The same refers to the raising of qualification of female workers. The percentage of women making use of their knowledge in creative sphere is still lower, and the number of women pa1taking in rationalization of production constitutes only 5.6%. A considerable number of women regard their private living conditions and their household duties being the main obstacle to the growth of their general education and their qualificational progress. Thanks to the extension of the network of children institutions and the system of social service women have more time of their own and, naturally, it leads to the growth of their education, qualification and raises the efficiency of their labour.